Delivering the Millennium Development Goals to Reduce Maternal and Child Mortality : A Systematic Review of Impact Evaluation Evidence - Independent Evaluation Group (World Bank, Washington, DC, 2016)
Improved outcomes for women and children - more education, lower fertility rates, higher nutritional status, and lower incidence of illness, among other outcomes - have broad individual, family, and societal benefits. For nearly 15 years, the targets of the millennium development goals (MDGs) have been a bellwether for progress, particularly for maternal and child health (MCH) - a two-thirds reduction in under-five mortality in MDG 4 and a three-quarters reduction in the maternal mortality ratio in MDG 5. This systematic review by the Independent Evaluation Group (IEG) is a learning exercise that looks beyond World Bank experience. It is intended to be used a reference for practitioners in the Bank and elsewhere with an interest in interventions that have demonstrated attributable improvements in skilled birth attendance and reductions in maternal and child mortality. This review also identifies important gaps in the impact evaluation evidence for interventions that may be effective in reducing maternal and child mortality but whose impacts have not yet been tested using robust impact evaluation methods. The systematic review provides findings on what is known about the effects of interventions on skilled birth attendance, maternal mortality, neonatal mortality, infant mortality, and under-five mortality, as well as the effect of skilled birth attendance on these and other intermediate MCH outcomes. Finally, the review highlights the main gaps in the body of impact evaluation knowledge for maternal and child mortality.